Augmented reality pictorial storybook: How does it influence on elementary school mathematics anxiety? - Azmil Hasan Lubis; Muhammad Darwis Dasopang; Fitri Ramadhini; Efrida Mandasari Dalimunthe (Universitas PGRI Madiun, 2022)
This study aims to explore the effect of media Augmented reality pictorial storybook on the anxiety of elementary school students in mathematics learning. This study used a quantitative approach with a quasi-experimental type of research. The experimental design used was a pretest-posttest control group design. The sample of this study was 60 students of fifth grade elementary school which were divided into two groups, namely the experimental group and the control group. The sampling technique used is cluster random sampling. The data were collected by using a mathematical anxiety questionnaire which was analyzed by means of a comparison technique, score trend test, and t-test. The results showed that the use of Augmented reality pictorial storybooks can reduce students' anxiety levels in mathematics learning. This can be seen from the average value of the pretest and posttest in the experimental class which showed a more significant decrease in anxiety towards mathematics learning (47.73%) than the decrease in anxiety in the control class (4.73%). The t-test results show that the significance value is 0.00 (<0.05), which means that Augmented reality pictorial storybooks have a significant effect on students' anxiety in mathematics learning.